DAMPAK JUDI ONLINE TERHADAP DISORGANISASI SOSIAL DI KALANGAN MAHASISWA BANDUNG - Aulia Fitri, Andini; Laila Salsabila, Zahra; Marlina, Lina (At-Tawazun, Jurnal Ekonomi Syariah, 2025)
The rise of online gambling practices among students is an increasingly worrying issue amid the rapid advancement of digital technology. This study aims to identify the factors that cause student involvement in online gambling and examine the social, psychological, economic, and academic impacts it causes. Using a descriptive qualitative approach, data was collected through literature studies and in-depth interviews. The findings show that internal impulses such as curiosity, economic pressure, and the expectation of instant profits, as well as external factors such as the influence of a friendly environment and ease of internet access, contribute greatly to the increase in student participation in online gambling. This activity has been proven to cause various negative consequences, including financial losses, mental disorders, decreased learning achievement, and potential legal problems. In response, integrated efforts are needed in the form of increasing financial literacy, strengthening regulations on online platforms, and active support from families, campuses, and the government in tackling the spread of online gambling in the student environment.